Comparison amount of microphthalmia-associated transcription factor in vitiligo before and after narrowband-ultraviolet B therapy - M. Yulianto Listiawan; Linda Astari; Putri Hendria Wardhani (PAGEPress Publications, 2019)
Vitiligo is the most commonly seen depigmentation disease with clinical manifestations of milk colored white macules, complex pathogenesis that is not well understood so that evolution of the disease is unpredictable and therapeutic outcomes are often unsatisfactory. Until now narrowband-ultraviolet B (NB-UVB) is considered the most effective and safe treatment for vitiligo. Therapy evaluation by looking at melanocytes function that can be seen with microphthalmia-associated transcription factor (MITF) immunohisto - chemistry will become more objective and accurate. This is a comparative analytic experimental study using pre-post test method comparing MITF in vitiligo patients before and after receiving NB-UVB conducted at Dr. Soetomo general hospital Surabaya, 12 vitiligo samples treated only with NB-UVB twice a week until 8 times therapies. The first exposure dose was 200 mJ and gradually increased 20% every therapy. Biopsy was performed before and after therapies and then MITF was compared. There was a significant difference between the amount of MITF in vitiligo before NB-UVB and after NB-UVB therapy stastistically, p=<0.001 (p=0.05). MITF is useful for indicators of treatment success.